Glycans as targets for therapeutic antitumor antibodies. (August 2012) - Rabu, Catherine; McIntosh, Richard; Jurasova, Zuzana; Durrant, Lindy
Glycans represent a vast class of molecules that modify either proteins or lipids. They exert and regulate important and complex functions in both normal and cancer cell metabolism. As such, the most immunogenic glycans have been targeted in passive and active immunotherapy in human cancer for the past 25 years but it is only recently that techniques have become available to uncover novel glycan targets. The main focus of this review article is to highlight why and how monoclonal antibodies (mAbs) recognizing glycans, and in particular the glycans expressed on glycolipids, are being used in various strategies to target and kill cancer cells. The article reports on the historical use of mAbs and on very recent progress made in antitumor therapy using the anti-GD2 mAb and the antiganglioside mAbs, anti- N -glycolylneuraminic acid mAb and anti-Lewis mAb. Anti-GD2 is showing great promise in Phase III clinical trials in adjuvant treatment of neuroblastoma. Racotumomab, an anti-idiotypic mAb mimicking N -glycolylneuraminic acid-containing gangliosides, is currently being tested in a randomized, controlled Phase II/III clinical trial. This article also presents various strategies used by different groups to develop mAbs against these naturally poorly immunogenic glycans.